Early Detection of Growth Impairment among Children and Adolescents with Eating Disorders: A Cross-Sectional Correlational Study - Purnamasari, Anisa; Zoahira, Wa Ode Aisa; Romantika, I Wayan; Apriyanti, Apriyanti (Journal of Applied Nursing and Health, 2025)
Background: The growth and development of children and adolescents are influenced by multiple factors, including nutrition, physical health, and psychosocial balance. Eating disorders (EDs) are among the conditions that can significantly disrupt this process, both physiologically and psychologically. Global and local data indicate a rising prevalence of eating disorders among adolescents, which negatively impacts nutritional status and physical growth. This study aims to identify and analyze the relationship between the risk of eating disorders and growth disturbances in children and adolescents based on anthropometric indicators. Methods: This study employed a quantitative, cross-sectional correlational design and was reported by the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines. A total of 120 participants aged 10–18 years from three schools in Kendari City were included. The risk of eating disorders was measured using the Eating Attitudes Test (EAT-26), while growth status was assessed through measurements of body weight, height, and body mass index (BMI), based on WHO standards. Data were analyzed using Spearman’s correlation test and multiple linear regression to evaluate the association and predictive effect of EAT-26 scores on growth indicators, controlling for age and gender. Results: A total of 39.2% of respondents had EAT-26 scores ≥20, indicating a risk of eating disorders. There was a significant negative correlation between EAT-26 scores and BMI (r = -0.421; p < 0.01), height (r = -0.315; p < 0.01), and weight (r = -0.386; p < 0.01). Multiple linear regression analysis revealed that EAT-26 scores significantly predicted BMI (β = -0.373; t = -4.698; p < 0.001), after controlling for age and gender, with an R² of 0.198. In contrast, age (p = 0.125) and gender (p = 0.262) did not show significant effects. These findings indicate that the risk of eating disorders significantly contributes to decreased nutritional status, regardless of age and gender. Conclusion: Eating disorders significantly contribute to impaired nutritional status and growth in children and adolescents. EAT-26 scores were negatively correlated with BMI, body weight, and height, and served as a significant predictor of BMI, while age and gender showed no significant effects. Early detection of eating disorder risk within school settings is crucial to prevent long-term impacts on adolescents' physical growth and health. Screening tools such as the EAT-26 can serve as effective initial instruments in promotive and preventive health programs.